Reproducible abscopal effect in a patient with lung cancer who underwent whole‐brain irradiation and atezolizumab administration - Hotta, Takamasa (Thorac Cancer, 2021)
Due to the emergence of immune checkpoint inhibitors, the abscopal effect has gained more attention. We report a case of extracranial abscopal effect after whole‐brain irradiation therapy due to brain metastasis. After the initial abscopal effect was confirmed, a second abscopal effect was confirmed following radiation therapy for bone metastases. This case confirms the reproducibility of the abscopal effect. Moreover, the abscopal effect was not observed in metastatic lesions with low immunogenicity, even in the same patient.